Are People Who Die by Intentional Medication Poisoning Dispensed Those Medications in the Year Prior to Death? - Boggs, Jennifer M.; Simon, Gregory E.; Beck, Arne; Rossom, Rebecca C.; Lynch, Frances L.; Lu, Christine Y.; Owen-Smith, Ashli A.; Waring, Stephen C.; Ahmedani, Brian K. (Archives of suicide research, 2023)
The rate of suicidal poisoning in the United States has increased substantially over the past 20 years. Understanding whether prescription medications used for self-poisoning were recently dispensed would help inform suicide prevention efforts. Alternatively, medications for self-poisoning could have been formerly dispensed or collected from friends, family, or illicit sources. Among those who died by intentional opioid and psychotropic poisonings, we conducted a descriptive study to determine what proportion had a recently filled prescription that could have been the means of suicide. Subjects were all people who died by intentional poisoning across nine health-care systems within the NIH-funded Mental Health Research Network. Among the 3,300 people who died by suicide, 700 died by any poisoning and 194 died by intentional opioid or psychotropic/hypnotic medication poisoning. Among those who died by intentional opioid poisoning 73% were dispensed an opioid in the year prior. Among those who died by intentional psychotropic/hypnotic poisoning, 83% were dispensed any psychotropic and 61% were dispensed a hypnotic in prior year. Most people were continuously dispensed the same medications used in their intentional poisonings in the year prior to death. Our results indicate that most medications used in suicidal overdose were likely recently dispensed. Therefore, future suicide prevention studies and prevention resources should focus on medication safety interventions such as lethal-means counseling for medication access, limiting quantities dispensed, opioid antagonists, and blister packs. HIGHLIGHTSUnderstanding whether medications used for self-poisoning were recently dispensed or formerly/never dispensed would help inform future studies and suicide prevention efforts.We found that most people who died by intentional poisoning with opioids or psychotropic/hypnotic medications received frequent dispensings of the medication used for self-poisoning in the year prior to death.Future suicide prevention studies and efforts should focus on medication safety interventions such as lethal-means counseling for medication access, limiting quantities dispensed, opioid antagonists, and blister packs.